Hepatocellular Carcinoma Diagnosis by Detecting α-Fucosidase with a Silicon Nanowire Field-Effect Transistor Biosensor. (20th April 2018) - Yang, Chao-Yu; Chiang, Hsu-Cheng; Kuo, Chia-Jung; Hsu, Chia-Wei; Chan, Shih-Feng; Lin, Zong-Yan; Lin, Chun-Hung; Chen, Yit-Tsong
Abstract : Hepatocellular carcinoma (HCC) is one of the most frequent and fatal cancers. However, traditional clinical imaging modalities cannot detect small tumors and are not suitable for the early stage diagnosis of hepatic cancer. In this study, we applied silicon nanowire field-effect transistors (SiNW-FETs) as a biosensor to detect α-fucosidase (AFU), which is a biomarker of high sensitivity and specificity for the HCC diagnosis. Fuconojirimycin (FNJ) is an inhibitor of AFU with very high binding affinity to AFU. By modifying the FNJs of optimized receptor length and number density on SiNW-FET (referred to as FNJ/SiNW-FET), this biosensing device can detect AFU to a very low concentration level with the detection limit of ∼1.3 pM. With the merits of high sensitivity, target specificity, and label-free detection, this FNJ/SiNW-FET can be developed as a powerful biosensor to detect AFU for the early HCC diagnosis.